Proceedings of the 4th International Workshop on Multicore Software Engineering (IWMSE'11) - Philippsen, Michael; Pankratius, Victor (ACM, 2011)
The number of cores per chip is still increasing. Currently, we have general-purpose processors with 48 cores and graphics cards with over 300 specialized cores. At the same time, there is a new trend: Heterogeneous multicore systems became available that combine general-purpose cores and graphics cores on the same chip. In the light of these developments, software needs to catch up. IWMSE 2011 is the fourth workshop in a series that continues its mission to advance the state of the art in multicore software engineering. The call for papers attracted 18 submissions by 49 authors from all over the world. The review process was double blind. The program committee finally accepted 6 full papers and 1 position paper that cover a variety of topics, including performance engineering, programming approaches, refactoring, and case studies.